Primary and Secondary/ Metastatic Salivary Duct Carcinoma Presenting within the Sinonasal Tract - Agaimy, Abbas; Müller, Sarina Katrin; Bishop, Justin A.; Chiosea, Simion I. (Head and Neck Pathology, 2021)
Traditionally, sinonasal adenocarcinomas have been subdivided into intestinal (ITAC) and non-intestinal (non-ITAC) categories. The latter encompasses salivary-type adenocarcinomas originating from the seromucinous glands of the sinonasal mucosa and non-salivary adenocarcinomas. The non-salivary adenocarcinoma category is further subdivided into low-and high-grade variants. Among salivary-type sinonasal adenocarcinomas, tumors recapitulating salivary duct carcinoma (SDC) are exceedingly rare, but some might have been lumped into the high-grade non-ITAC category. To date, only three primary SDCs originating in the sinonasal tract have been reported. We herein describe 7 cases of SDC including one previously reported case (4 primary sinonasal, 3 metastatic/ extension from parotid gland SDC). The primary tumors affected 3 males and one female aged 60 – 75. Different sites were involved by the primary tumors while the secondary tumors affected the sphenoidal (2) and the frontal + maxillary (1) sinuses. Three primary tumors were de novo high-grade SDC and one was confined to contours of a pre-existing pleomorphic adenoma. All 3 secondary tumors were SDC ex pleomorphic adenoma of the parotid with a long history of recurrences, ultimately involving the sinonasal tract. Androgen receptor was positive in 7/7 cases. Four of 6 cases were strongly HER2/neu + (either score 3 + or with verified amplification). This small case series adds to the delineation of primary sinonasal SDC highlighting that almost half of invasive SDC presenting within sinonasal tract indeed represents extension or metastasis from a parotid gland primary. There is a tendency towards overrepresentation of HER2/neu-positive cases in both categories (primary and metastatic), but this needs clarification in larger studies.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Carcinoma ex pleomorphic adenoma; Ductal adenocarcinoma; HER2/neu; Non-intestinal adenocarcinoma; Salivary duct carcinoma; Sinonasal tract